Futebol feminino: componentes corporais, desempenho físico, ansiedade e Covid-19. Perfil e possível associação entre as variáveis - Licen, Renata Palermo (2023)
Soccer is one of the most popular sports in the world and female athletes have conquered their space in this sport, being recognized worldwide. Athletic performance is the result of multifactorial aspects and with the pandemic of COVID-19, the impact that the virus can cause on athletic performance is still not well established. Therefore, this study aims to analyze the possible relationships between the signs and symptoms of COVID-19 and the levels of anxiety, aerobic capacity, muscle mass and power of lower limbs of professional female soccer athletes. This is a cross-sectional, retrospective, analytical study. The study group was composed of 129 female soccer athletes playing professionally in national and international sports. Body composition, lower limb power, and aerobic capacity data were obtained from the database provided by the clubs, and data regarding COVID-19 signs and symptoms and anxiety were obtained through an online questionnaire. Pearson's and Spearman's linear correlation coefficient was used. All analyses were performed with the Statistical Package for Social Sciences (SPSS), version 22.0, adopting a significance level of 5%. There was a positive correlation only between trait anxiety and COVID-19 signs and symptoms in female soccer athletes. The following signs and symptoms of COVID-19 stood out: fever, fatigue, nasal congestion and headache, persisting for more than 15 days, fatigue and hyposmia. Most of the athletes stayed away for 10 to 12 days, however, two athletes stayed away from training for 1 year. Most of the athletes reported feeling well enough to return to training after this period, and of the athletes who did not feel well, the main complaint was fatigue, followed by shortness of breath and muscle fatigue. Although most of the athletes reported not being afraid, anxious or nervous to return to their activities, they did not present themselves with high expectations or motivation to return to play. It was found that the investigated athletes had a state anxiety considered medium (most) and a trait anxiety considered high (most); aerobic capacity (most) "good" or "excellent"; and lower limb strength consistent with professional athletes' results. It was also observed that COVID19 signs and symptoms are related only to trait anxiety, with no relation to state anxiety, lower limb power, or aerobic capacity.